2009
DOI: 10.1186/1471-2164-10-20
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTL affecting resistance to Marek's disease in an F6 advanced intercross population of commercial layer chickens

Abstract: Background: Marek's disease (MD) is a T-cell lymphoma of chickens caused by the Marek's disease virus (MDV), an oncogenic avian herpesvirus. MD is a major cause of economic loss to the poultry industry and the most serious and persistent infectious disease concern. A full-sib intercross population, consisting of five independent families was generated by crossing and repeated intercrossing of two partially inbred commercial White Leghorn layer lines known to differ in genetic resistance to MD. At the F6 genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 42 publications
7
36
1
2
Order By: Relevance
“…It is reported that the QTL for MD resistance and susceptibility were mapped to several chromosomes, including GGA 1-5, 7-9, 15, 18, 26, Z, E21, and E16, by using the backcross or intercross populations (Heifetz et al 2007, 2009; Liu et al 2001; Vallejo et al 1998). To identify whether common genomic variants were detected by using different methods, we compared our CNVs with the QTL regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the QTL for MD resistance and susceptibility were mapped to several chromosomes, including GGA 1-5, 7-9, 15, 18, 26, Z, E21, and E16, by using the backcross or intercross populations (Heifetz et al 2007, 2009; Liu et al 2001; Vallejo et al 1998). To identify whether common genomic variants were detected by using different methods, we compared our CNVs with the QTL regions.…”
Section: Resultsmentioning
confidence: 99%
“…The MD-related QTL information was downloaded from Chicken QTLdb (http://www.animalgenome.org/cgi-bin/QTLdb/GG/index), which converted the QTL positions from genetic distance (cM) to the physical distance (bp) by using the mapping data from previous research (Heifetz et al 2007, 2009; Liu et al 2001; Vallejo et al 1998). When there is more than 100 bp overlap between CNVs and QTL, we consider that region as shared region.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, vaccination with low oncogenic RSV strains induces not only protective immunity but also results in regression of visceral tumors and erythroblastosis induced by RSV [165]. Finally, contribution of non-MHC genes in resistance to viral replication and tumor growth is also documented [162, 166]. …”
Section: Tumor Immunitymentioning
confidence: 99%
“…This has been determined predominantly in studies of the MHC-congenic lines 6 1 (resistant) and 7 2 (susceptible), which were developed in East Lansing, MI, which differ in their resistance to a large number of MDV isolates (38). Several potential MD resistance quantitative trait loci (QTL) have been identified from crosses between these lines and others (48,52,33,11,19), but relatively few actual genes have been associated with the disease. Those which have been identified include growth hormone (GH1) (27,30), small inducible cytokine subfamily C member 1 (SCYC1) (29), and stem cell antigen 2 (SCA2) (31).…”
mentioning
confidence: 99%